Joint Scheduling and Power Allocation with Per-User Rate Constraints for Uplink MU-MIMO OFDMA Systems - Zhang, Lin; Han, Shengqian; Yang, Chenyang (IEEE Vehicular Technology Conference, 2023)
This paper studies the joint scheduling and power allocation for uplink multiuser multi-input multi-output (MU-MIMO) orthogonal frequency division multiple access (OFDMA) systems. The objective is to minimize the number of occupied resource blocks (RBs) subject to per-user rate constraints. The problem is a mixed integer and non-convex programming problem. We first propose a hierarchical algorithm to find a solution, where in the outer layer the number of RBs are reduced in a greedy manner while in the inner layer the power allocation and scheduling of users are optimized to determine which RB should be unoccupied. The inner problem is non-convex high-complexity problem. To reduce the complexity, we further employ a deep neural network to learn the solution of the inner problem. Simulation results show that compared to two baseline methods, the proposed method can effectively reduce the occupied RBs with much lower complexity.